Voice assistance in task-based learning to mediate EFL texts - Gajewska, Klaudia (Neofilolog, 2025)
The research into voice assistance indicating a positive effect of the application of voice-controlled software on language learning can be challenged in view of its methodological limitations. Also, little is known about the technology use in Task-Based Language Learning (TBLL) as only one empirical study has been undertaken with this aim so far. To address these research gaps, we conducted a quasi-experimental study investigating the use of the Alexa voice assistant (VA) in the novel context of TBLL to mediate texts. 63 Polish intermediate learners of English as a foreign language (EFL), randomly assigned into experimental and control groups, participated in a nineteen-week quasi-experiment using a factor rotation technique. The effects of the treatment, in which Alexa was used for source texts during task performance, were examined with regard to changes in the participants’ intralinguistic text mediating ability at within- and between-group levels. The statistical analysis of the pre- and post-tests revealed that the intervention involving Computer-Assisted Language Learning (CALL) combined with TBLL had a positive impact on participants’ mediation skills. The findings advance the limited understanding of VA application in TBLL by showing the potential of integrating voice assistance with task-oriented homework for improving learners’ ability to mediate texts .